Reporte de un caso de granuloma hiperqueratósico producido por Candida albicans - Mata, Leonardo (1958)
A case is described of hyperkeratosic cutaneous granuloma caused by C. albicans, in a 2 1/2 year-old girl, of white race. The area affected comprised the scalp, face, trunk, limbs, and fingernails.